Repair and Renovation of the Historic Church in Ruda Śląska after Many Failures Caused by Mining Exploitation - Drobiec, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper describes a case of the church, which for nearly 70 years was exposed to the impact of 26 mining exploitations conducted under the church or very close to the church at different depths. These caused damage in the form of superficial cracks of vaults and walls as well as the loosening of the front layer of stone façade of towers. The construction has been preserved due to the continuous monitoring and numerous repairs and renovations. Currently, there is no mining exploitation under the church.
Keywords: historic building; damage to masonry structures; repairs of historic building; effect of mining explotation; church in Ruda Śląska; obiekty zabytkowe; uszkodzenia konstrukcji murowanych; remonty obiektów zabytkowych; skutki eksploatacji górniczej; kościół w Rudzie Śląskiej